Role of magnetic resonance imaging in the evaluation of seizures - Dhar, Namrita; Magotra, Vipan (International Journal of Research in Medical Sciences, 2022)
Background: A seizure is a clinical condition caused by a transitory event of unusual unrestrained or recurring neuronal activity in the brain.Repeated unprovoked seizures are described as epilepsy. Seizures and epilepsy are major public health problems in developing countries like India with a serious impact on patients and society. The objective of the present study is to evaluate the magnetic resonance imaging (MRI) findings in patients with seizures. Methods: This cross-sectional observational study was conducted in the Department of Radiodiagnosis and Imaging, Government Medical College, Jammu on 125 patients referred with clinical features of seizures. Results: In the present study, MRI findings were normal in 58 (46.4%) cases and revealed a spectrum of abnormalities in 67 (53.6%) cases. Out of 67 abnormal MRI findings, the common abnormalities noted were – neurocysticercosis (NCC) in 11 patients(8.8%), tuberculoma in 9 patients (7.2%), tumors in 7 patients (5.6%), hypoxic ischemic insult in 8 patients (6.4%), developmental cortical malformations in 6 patients (4.8%), encephalitis in 4 patients (3.2%), phakomatosis in 5 patients (4.0%), chronic infarct in 4 patients (3.2%), traumatic brain injury in 3 patients (3.2%), cavernoma in 2 patients (1.6%), mesial temporal sclerosis in 2 patients (1.6%), cerebral abscess in 2 patients (1.6%), and metabolic cause, multiple sclerosis, arterial infarct, and venous thrombosis, in one patient each respectively. Conclusions: From our study, it could be concluded that MRI has an outstanding place in the evaluation of patients presenting with seizures. The findings of the present study will be valuable in epilepsy management in developing country like ours and MRI will emerge as a beam of light amidst a storm of myth for patients with seizures.